Cellulose-based Adsorbent of Animal Waste for the Adsorption of Lead and Phenol - Patrick T. Ngueagni; Mohamed Hefnawy; Edwin Andrew Ofudje; Ali El Gamal; James Asamu Akande; Talha Bin Emran (BioResources)
The adsorption of phenol and Pb2+ from aqueous solutions was achieved using calcined animal waste (cow dung) as a low-cost adsorbent. Fourier transform infrared analysis confirmed the involvement of hydroxyl, carbonate, and possibly silicate functional groups in the adsorption process. Scanning electron microscope images revealed the presence of distinct rod-like fibers on the adsorbent surface. Adsorption kinetics revealed an increase in pollutant uptake over time, with the effect being more pronounced at a higher initial concentration of 280 mg/L. The optimal pH for maximum adsorption was identified as 6.5 for phenol and 4.5 for lead. Langmuir isotherm analysis indicated a higher adsorption affinity for lead, with a maximum adsorption capacity of 101 mg/g, compared to 89.3 mg/g for phenol. Conversely, the Freundlich isotherm model demonstrated a better fit for phenol adsorption. Thermodynamic evaluations showed negative ΔG° values, confirming the spontaneous nature of the sorption process for both pollutants. The enthalpy change (ΔH°) values of 11.6 kJ/mol for phenol and 21.7 kJ/mol for lead validated the endothermic nature of the adsorption. These results underscore the effectiveness of calcined animal waste as a sustainable and efficient adsorbent for eliminating phenol and lead from wastewater.